Algorithm for received signal in multipath propagation conditions - Chernyshov Dmitry (E3S Web of Conferences, 2019)
This article discusses the received signal reception algorithm under conditions of multipath propagation of radio waves. As well as an analytical expression of the effectiveness of this algorithm is derived from the point of view of SNR.